Investigating the Variations in Water Requirement for Main Plants in the Cultivation Pattern (Case Study: Kashmar Plain of Khorasan Razavi) - Hadi Dehghan; Somayeh Galdavi (Water Harvesting Research)
The agricultural sector is crucial to Iran's economy, especially in ensuring food security. Climate changes, intense competition for water resources among various sectors, and the declining share of renewable resources in the agricultural sector make managing water consumption in agriculture essential. When doing so, it's important to consider changes in plant water needs. This study investigated the process of changing the water requirement of plants in the cultivation pattern in the Kashmar Plain by calculating evapotranspiration. These plants are including Sunflower, Leafy vegetables, Potato, Apple, Lentils, Walnut, Pears, Wheat, Tomato, Cherries, Peach, Watermelon, Peas, Vegetables, Pistachio, Plum, Pomegranate, Grape, Almonds, Eggplant, Cotton, Onion, Barley, Sugar beet, Melon, Spring cucumber, Autumn cucumber, Fodder corn, Saffron, and Cantaloupe. Firstly, the reference evapotranspiration was calculated on a daily scale over 20 years (1998 to 2017) using the FAO Penman Monteith equation. Then, monthly, seasonal, and annual values were used for calculations, and cultivated plants' evapotranspiration (water requirement) (ETc) was determined. The Mann-Kendall test was utilized to examine the changes in Evapotranspiration of plants. The results indicated an increasing trend in the water requirement of plants in the region. The greatest increases were observed in Evapotranspiration for autumn cucumber plants (54.8% increase), sugar beet (41.51% increase), and pistachio (38% increase), while the lowest increase was seen in almonds at 3.07%. After analyzing the data, it was found that pomegranates (19.94% increase) and lentils (20.54% increase) have the lowest increase in evaporation, transpiration, and water requirement. This suggests that changes in the cultivation pattern of the region may be necessary due to the varying water requirements of different plants. The findings of this research could be valuable in making decisions about the cultivation pattern of plants in the region.